Effects of Sodium Chloride Salinity on Water Relations and Ion Accumulation in Two Mungbean Varieties Differing in Salinity Tolerance - Sultana, Mst Shahnaz; Halim, MA; Hossain, Feroza; Karim, M Abdul; Hossain, Mohammad Talim (Journal of the Asiatic Society of Bangladesh, Science, 2019)
Salt tolerance in relation to water status and plant nutrients of two mungbean varieties, BARImung 2 (salinity sensitive) and BUmung 2 (salinity tolerant) was evaluated. The seeds were grown in pots and treated with NaCl levels of 0 (control), 100 and 200 mM. Different parameters related to water relations as well as mineral nutritients were measured. The exudation rate and relative water content were decreased but water saturation deficit was increased by salinity in both the varieties. In BARImung 2 plants, the exudation rate and relative water content were lower but water saturation deficit was higher than those in BUmung 2 at both 100 and 200 mM NaCl levels. Salinity also influenced the accumulation of Na, K, Ca and Mg in leaves, stems and roots of the two said mungbean varieties. Sodium accumulation was inceseased in all the plant-parts of both the varieties in the order of stem > root > leaf but in BUmung 2 the accumulation was lower than that of BARImung 2 except in root. Potassium accumulation deceresed in all parts of both the mungbean varieties but that was lower in BUmung 2 than that of BARImung 2. The contents of Ca and Mg in all the plant-parts increased more in BUmung 2 than those of BARImung 2 with the increase of salinity levels. All these results indicated that high salt tolerance in BUmung 2 was associated with its better water status, more or less uniform mineral nutrient (Ca and Mg) distribution in different plantparts than that in BARImung 2. Asiat. Soc. Bangladesh, Sci. 45(1): 45-54, June 2019